Responsabilidade civil médica em face das técnicas de reprodução humana assistida - Avelar, Ednara Pontes de (2008)
The present work aims to research the medical civil responsibility due to the techniques of assisted human reproduction. To face the subject, it initially makes a brief study of the medical aspects of those procedures. Soon after, it analyzes their main juridical implications, such as: the destiny of the exceeding embryos; the gestation contract by somebody else; the donor s anonymity and the right to the genetic identity. Since then, it develops the central theme of the work, going by the examination of the incidence of the Code of Consumer s Defense in the relationships doctor-patient; of the nature of the obligation assumed by the doctor in those contracts of rendering of services: if of mean or of result; of the importance of the informed consent in the assisted procreation. It still searches the general aspects of the medical mistake, of the medical blame and of the medical damage, for in succession to treat the specific aspects of the recovery duty by the doctors, of the clinics of assisted human reproduction and of the banks of deposit of fertilizing material. At the end, it appreciates hypothetical cases that were presented to law operators, in order to have their opinions